Liver transplantation after paracetamol overdose. Issue 6796 (27th July 1991) - O'Grady, J G; Wendon, J; Tan, K C; Potter, D; Cottam, S; Cohen, A T; Gimson, A E; Williams, R
Abstract : OBJECTIVE--To evaluate the role of liver transplantation after paracetamol overdose. DESIGN--Prospective study of consecutive candidates for transplantation and performance of transplantation over 18 months. SETTING--Liver unit, King's College Hospital, London. MAIN OUTCOME MEASURES--Fulfilment of indicators of poor prognosis, selection for transplantation, transplantation, survival. RESULTS--30 of 37 patients considered to have a reasonable prognosis with intensive medical care survived. Of 14 of 29 patients considered to have a very poor prognosis and registered for urgent liver transplantation, six received liver transplants, four of whom survived, while seven died and one survived without a transplant. Three of 15 patients with poor prognostic indicators but not selected for transplantation survived. CONCLUSION--Liver transplantation will have a definite but limited role in the management of fulminant hepatic failure induced by paracetamol.